Un tablet subacqueo per la documentazione e la fruizione dei siti archeologici sommersi - Bruno, Fabio; Petriaggi, Barbara Davidde; Mangeruga, Marino; Cozza, Marco (Archeomatica, 2018)
Within the i-MareCulture and Lab4Dive projects, an international partnership is developing different technologies for both in-situ and virtual underwater exploration. In particular, an underwater tablet dedicated to the archaeological sites is being developed to improve the recreational diving experience and support the research activities conducted by the archaeological divers. This tablet allows the diver to recognize his position in the underwater site, to acquire geo-localized photos and notes and to visualize the hypothetical reconstruction of the underwater remains through the augmented reality. In addition, it has been realized a virtual diving application that enables every user to explore some different underwater archaeological sites of the Mediterranean Sea without the need to conduct a proper dive. This virtual visit can be enjoyed by means of different Head Mounted Displays (HMDs), such as the HTC Vive, the Samsung Gear VR or the Google Daydream, exploiting the features of these devices to interact with the virtual environment. During the visit, additional information can be obtained playing some videos realized with the typical approach of the storytelling and a 360° field of view.